2019
DOI: 10.1136/rmdopen-2019-000951
|View full text |Cite
|
Sign up to set email alerts
|

Six-month prospective trial in early and long-standing rheumatoid arthritis: evaluating disease activity in the wrist through sequential synovial histopathological analysis, RAMRIS magnetic resonance score and EULAR-OMERACT ultrasound score

Abstract: IntroductionStandardised scoring systems for rheumatoid arthritis (RA) joint disease activity include Larsen score for radiographs, rheumatoid arthritis magnetic resonance imaging score (RAMRIS) for MRI and using the European League Against Rheumatisms-Outcome Measures in Rheumatology (EULAR-OMERACT) score for ultrasound (US) images. The aim of this prospective study was to investigate the relationship between histological synovitis and radiological synovitis, assessed by conventional X-ray, US and MRI of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Next, we investigated which types of specific lipids best represent synovitis severity, as determined by ultrasonography (which reflects histological synovitis) 27 , 28 . The severity of synovitis was assessed by ultrasonography at the time of SF aspiration.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated which types of specific lipids best represent synovitis severity, as determined by ultrasonography (which reflects histological synovitis) 27 , 28 . The severity of synovitis was assessed by ultrasonography at the time of SF aspiration.…”
Section: Resultsmentioning
confidence: 99%
“…Data from this cohort comparing wrist synovial biopsy inflammation with disease activity in the wrist by X-ray, ultrasound and MRI have been published separately. 20 Overlapping results are a description of ultrasound and MRI data, synovial inflammation and RA disease activity. In this article, we use the Larsen score for all joints of the biopsied hand and not only the biopsied wrist.…”
Section: Methodsmentioning
confidence: 99%
“…29 On the same side as the USGSB procedure was to be performed, an MRI of the hand and wrist was performed, as previously described. 20 MRI was performed for a maximum of 2 hours before the biopsy procedure for all at baseline and also at 6 months for ERA. Using the RAMRIS system, a consultant in radiology (TT) scored all examinations.…”
Section: Methodsmentioning
confidence: 99%
“…They found that EULAR-OMERACT ultrasound score and RAMRIS MRI score were strongly correlated with Krenn's synovitis score at baseline, but not 6-month assessment, in the early RA group. In the established RA group, a moderate to strong correlation was present between the three scores at baseline assessment, except for the RAMRIS 6-month assessment, which was not performed (53).…”
Section: Quality and Quantity Of Synovial Samples Collected By Usgsbmentioning
confidence: 89%